2020
DOI: 10.21037/atm-20-4441
|View full text |Cite
|
Sign up to set email alerts
|

The potential adjunctive benefit of adding metformin to standard treatment in inoperable cancer patients: a meta-analysis of randomized controlled trials

Abstract: Background: Recently, there have been several randomized clinical trials (RCTs) conducted to evaluate the efficacy and safety of metformin plus standard treatment in inoperable cancer patients. Our meta-analysis aimed to assess the efficacy of metformin in combination with standard treatment in inoperable cancer patients.Methods: PubMed and Embase databases were systematically searched for relevant RCTs investigating the efficacy of adding metformin to standard treatment for cancer patients. The pooled relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Our results suggest that the addition of metformin to chemotherapy or endocrine therapy may have little efficacy in nondiabetic patients with metastatic/recurrent breast cancer. A meta-analysis 14 reported that adding metformin to standard treatment improved the overall response rate (ORR) in patients with metastatic breast cancer compared with standard treatment alone but did not improve OS and PFS. There are some differences in the methods used between the present study and the Wu et al study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results suggest that the addition of metformin to chemotherapy or endocrine therapy may have little efficacy in nondiabetic patients with metastatic/recurrent breast cancer. A meta-analysis 14 reported that adding metformin to standard treatment improved the overall response rate (ORR) in patients with metastatic breast cancer compared with standard treatment alone but did not improve OS and PFS. There are some differences in the methods used between the present study and the Wu et al study.…”
Section: Discussionmentioning
confidence: 99%
“…There are some differences in the methods used between the present study and the Wu et al study. 14 First, 2 empirical studies 24 showed a moderate correlation between the response rate and OS. However, no report showed that ORR is a potential surrogate for OS and PFS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, our preclinical data demonstrated that metformin represents anti-tumor/anti-metastatic effect only when prescribed with a DPP-4 inhibitor; nevertheless, metformin alone had no impact on basal breast cancer proliferation and metastasis in vivo [ 38 ]. Indeed, some randomized trials showed no impact of metformin on breast cancer progression and prognosis [ 141 , 142 , 143 ], even though several preclinical data have reported the anti-tumor effect of metformin in breast cancer. Further mechanistic investigation is definitely needed, using metformin as an anti-tumor agent in a clinical setting.…”
Section: Perspective: Co-prescription With Metforminmentioning
confidence: 99%
“…Recently, as epidemiologic data supported metformin may reduce cancer risk in diabetics, metformin has drawn attention in both cancer prevention and therapy 4,5 . Repurposing metformin as a cancer treatment is being tested in a wide range of clinical trials for a variety of cancers, including renal cell carcinoma, head and neck carcinomas and pancreatic carcinoma 3,6,7 . In addition, combining metformin with chemotherapies has been attempted in various cancers 1,8,9 .…”
Section: Introductionmentioning
confidence: 99%